Implementasi Sistem Informasi Manajemen Keuangan Desa pada Desa Satriyan Kabupaten Batang - Miftahurrohman Miftahurrohman (LPPM Universitas Sains dan Teknologi Komputer, 2023)
The Village Financial Management Information System is needed as a solution for the village government in carrying out its functions. Especially in village financial management. This is based on village needs, where village financial management still uses the conventional model, namely planning a budget by writing it on a book and continuing with recording on the Ms. office application. Excel and the difficulty of data search processes, reporting systems. The arrangement of information that is carried out regularly, clearly, precisely and quickly and can be presented in applications and reports certainly greatly supports the smooth running of village government operations. By utilizing information technology the village government can interact and exchange information with residents and with other village governments so as to facilitate the running of the village government in providing services and information to the community.